Discrete-event simulation study of a COVID-19 mass vaccination centre. (February 2023) - Sala, Francesca; D'Urso, Gianluca; Giardini, Claudio
Highlights: The global spread of COVID-19 and the establishment of mass vaccination campaigns required the set-up of specific vaccination sites, known as Mass Vaccination Centres (MVCs), capable of handling large numbers of patients rapidly and safely. Multiple and different MVCs physical layout and organizational structures are present, leading to a certain grade of variation in the execution and performance of the vaccination process. The present study provided evidence on the efficiency of the vaccination campaign within a sports centre, operating with an organizational layout distinct from those available in the literature and those specified by the anti-COVID-19 guidelines. The work outlined a methodology, based on DES tools and techniques, for the study and analysis of health care processes. Abstract: The global spread of COVID-19 and the declaration of the pandemic status made by the World Health Organization (WHO) led to the establishment of mass vaccination campaigns. The challenges posed by the request to immunise the entire population necessitated the set-up of new vaccination sites, named Mass Vaccination Centres (MVCs), capable of handling large numbers of patients rapidly and safely. The present study focused on the evolution of MVC performances, in terms of the maximum number of vaccinated patients and primary resource utilisation ratio, while involving statistics belonging to the patient dimension. The research involved the creation of a digital model of the MVC, using the Discrete-Event Simulation (DES) software (FlexSim Healthcare), and consequent what-if analyses. The results were derived from the study of an existing facility, located within a sports centre in the province of Bergamo (Italy) and operating with an advanced MVC organisational model, in compliance with the national anti-SARS-CoV-2 legislation. The research provided additional evidence on innovative MVC organisational models, identifying an optimal MVC configuration. Besides, the obtained results remain relevant for countries where a significant portion of the population has not yet addressed the emergency, either for upcoming vaccination treatments. Furthermore, the methodology adopted in the present article proved to be a valuable resource in the analysis of the healthcare processes.